Breast diseases : imaging and clinical management - Selvi, Radhakrishna (Springer India Imprint: Springer, 2015)
It is challenging enough to be able to make a diagnosis in mammography, but the newer standards of care demand more than just providing a diagnosis. This book is an excellent resource to improve the understanding of breast diseases, recognize and manage problems encountered in breast imaging and clinical management of the breast diseases. With forty four chapters, this volume is divided into six sections on screening of breast cancer, imaging modalities, benign breast disorders, interventional procedures, pathological considerations and breast cancer. Breast Diseases: Imaging and Clinical Management is a crisp volume on clinical and multimodality breast imaging with emphasis on interventional procedures, pathology and the entire spectrum of breast cancers.  .